2013
DOI: 10.1080/00207543.2013.802052
|View full text |Cite
|
Sign up to set email alerts
|

When less is better: Insights from the product mix dilemma from the Theory of Constraints perspective

Abstract: Perhaps due to its origins in a production scheduling software called Optimised Production Technology (OPT), plus the idea of focusing on system constraints, many believe that the Theory of Constraints (TOC) has a vocation for optimal solutions. Those who assess TOC according to this perspective indicate that it guarantees an optimal solution only in certain circumstances. In opposition to this view and founded on a numeric example of a production mix problem, this paper shows, by means of TOC assumptions, why… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…The POOGI heuristics met with harsh criticism from academic community. The main reason of academic scepticism is the manner of products/jobs selection targeted to the constraint(s) utilization which does not give the optimal solution associated with maximizing net profit and return of investment in the long-term period (Ifandoudas & Gurd, 2010), (Souza, Sobreiro, Nagano & Manfrinato, 2013). In addition, the theory of constraints does not disclose the relationship between the operating activities of the production company and the valuation of products, although the price of each product is one of the key parameters for throughput calculation Ti.…”
Section: Theory Of Constraints As a Tool Of Decision-making Product-mix Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The POOGI heuristics met with harsh criticism from academic community. The main reason of academic scepticism is the manner of products/jobs selection targeted to the constraint(s) utilization which does not give the optimal solution associated with maximizing net profit and return of investment in the long-term period (Ifandoudas & Gurd, 2010), (Souza, Sobreiro, Nagano & Manfrinato, 2013). In addition, the theory of constraints does not disclose the relationship between the operating activities of the production company and the valuation of products, although the price of each product is one of the key parameters for throughput calculation Ti.…”
Section: Theory Of Constraints As a Tool Of Decision-making Product-mix Optimizationmentioning
confidence: 99%
“…Data for this example (in particular, unit processing times) are established in such a way that one of the machines is overloaded in a given period of time (there is always at least one machine/constraint incapable of producing all the products P and Q as results from demand). The problem is to decide on the number of products P and Q directed to the production in order not to exceed the total available time and to maximize the profit of the company (Souza et al, 2013). With the development of the theory of constraints PQ issue has evolved.…”
Section: Theory Of Constraints As a Tool Of Decision-making Product-mix Optimizationmentioning
confidence: 99%
“…Then Aryanezhad [6] and others tested RTOC, and found that RTOC sometimes got non-optimal solution, and optimized RTOC. De Souza et al [7] discussed the controversial issue of comparing TOC with the optimization method of product portfolio decision, and put forward a heuristic method to obtain feasible solutions from the perspective of TOC. The results are compared with those of integer linear programming.…”
Section: Introductionmentioning
confidence: 99%
“…Por exemplo, apesar de não citarem Goldratt (1990a), Hopp e Spearman (2001, p. 548-552) abordam o problema dos produtos P e Q para mostrar diferenças entre os resultados obtidos com a heurística da TOC e os obtidos através da programação linear, chegando à conclusão que a heuríitica da TOC pode resultar em resultados subótimos. Hodiernamente, o problema dos produtos P e Q ainda é utilizado em pesquisas acadêmcias sobre decisão de mix de produtos (ex: SOBREIRO;SOBREIRO;SOUZA et al, 2013), principalmente no que tange ao desenvolvimento de novas heurísticas e procedimentos matemáticos (segunda vertente de pesquisa sobre decisão de mix de produtos). "…”
Section: Abcunclassified